Pengembangan Bahan Ajar Pendidikan Agama Islam Menggunakan Pendekatan Ilmiah - Imam Muddin (Jurnal Pendidikan Islam Indonesia, 2019)
In Permendikbud No. 65 of 2013 concerning process standards, the characteristics of learning on curriculum 2013 use a scientific approach. The essence of the scientific approach curriculum learning includes: observing, asking, reasoning, trying, and communicating for all subjects, including Islamic Education. Teaching materials are one of the important components in advancing students in learning, especially in Islamic Education subjects that contain characteristics with a scientific approach, so that interactions can occur well for students, because the core of learning is the occurrence of interactions between students and learning resources. The core of the development of teaching materials is how to develop teaching materials with a scientific approach to the subjects of Islamic Education and how the results of the implementation of teaching materials with a scientific approach to PAI subjects. Based on the results of field trials, this teaching material general is good. This can be proven by responses, assessments made by the expert team, by using SPSS 16.0 calculations by testing the pretest, posttest on the control class, and the experimental class which confirms that there are differences significant between learning outcomes using teaching materials through a scientific approach.